Socioeconomic status as a predictor of post-operative mortality and outcomes in carotid artery stenting vs. carotid endarterectomy - Baxi, Jigesh; Chao, Joshua C.; Dewan, Krish; Yang, NaYoung K.; Pepe, Russell J.; Deng, Xiaoyan; Soliman, Fady K.; Volk, Lindsay; Rahimi, Saum; Russo, Mark J.; Lee, Leonard Y. (Frontiers in Cardiovascular Medicine, 2024)
The association between low socioeconomic status (SES) and worse surgical outcomes has become an emerging area of interest. Literature has demonstrated that carotid artery stenting (CAS) poses greater risk of postoperative complications, particularly stroke, than carotid endarterectomy (CEA). This study aims to compare the impact of low SES on patients undergoing CAS versus CEA.The National Inpatient Sample (NIS) was queried for patients undergoing CAS and CEA from 2010-2015. Patients were stratified by highest and lowest median income quartiles by zip code and compared through demographics, hospital characteristics, and comorbidities defined by the Charlson Comorbidity Index (CCI). Primary outcome was in-hospital mortality. Secondary outcomes included acute kidney injury (AKI), post-operative stroke, sepsis, and bleeding requiring reoperation.Multivariable logistic regression was used to determine the effect of SES on outcomes.Results: 5,425 patients underwent CAS (Low SES: 3,516(64.8%); High SES: 1,909(35.2%))and 38,399 patients underwent CEA (Low SES: 22,852(59.5%); High SES: 15,547(40.5%)).Low SES was a significant independent predictor of mortality (OR=2. 07[1.25-3.53]; p=0.005) for CEA patients, but not for CAS patients (OR=1.21[CI 0.51-2.30]; p=0.68). Stroke was strongly associated with low SES, CEA patients (Low SES=1.5% vs High SES=1.2%;p=0.03), while bleeding was with high SES, CAS patients (Low SES=5.3% vs High SES=7.1%;p=0.01). CCI was a strong predictor of mortality for both procedures (CAS: OR1.